Enzymatic Activity and Photo-Kinetic Study of Cr(III), Mn(II), Co(II), Ni(II) and Cu(II) Complexes with Tetradentate - M. Khamis, Wessal; S.H. Mohammed, Suhair; H. Abdullah, Amer; Gd. Sha`aban, Hanan; H. Abdul Sada, Shaemmaa; Azer Daher, Gwan (International Journal of Engineering and Technology, 2018)
The Photo kinetic studies for five metal complexes of tetradentate Schiff base ligand were studied. These complexes were Chrome, Manganese, Cobalt, Nickle and Copper complexes. The kinetic values were achieved for the photoreaction and it referred to first order by in terms of complexes concentration. Three concentrations of these complexes to determined rate constant value which were determined by calculation the slope (-k) of relationship between radiation time on X-axis and natural logathirm of concentration changing on Y-axis. Values of rate constant were (0.0317min-1) for Cr-complex, (0.054min-1) for Mn-complex, (0.0706min-1) for Co-complex, (0.133min-1) for Ni-complex and (0.1211min-1) for Cu-complex. Relation between concentration on Y-axis and radiation time were showed the decreasing of concentration with time. Enzymatic study for the five complexes were achieved and showed that Cr-complex and Mn-complex showed competitive reactions and uncompetitive for Co-complex, Ni-complex and Cu-complex.Â Â